Paracoccidioides brasiliensis 14-3-3 protein is important for virulence in a murine model - Marcos, Caroline Maria [UNESP] (2019)
The Paracoccidioides brasiliensis strain downregulated the expression of adhesin Pb14-3-3 (Pb14-3-3 aRNA) was evaluated in a murine model of paracoccidioidomycosis (PCM). Pb14-3-3 aRNA displays attenuated virulence and triggered the formation of fewer granulomas by lowering the fungal burden in the lungs. Additionally, the Pb14-3-3 aRNA showed more elongated yeast cells and less ability to induce pneumocytes apoptosis in vitro. Our results show that 14-3-3 is an important virulence factor in P. brasiliensis-induced pulmonary infection.